Properties of low density particleboard made from oil palm trunk (OPT) / Nur Afiqah Abd Halim - Abd Halim, Nur Afiqah (Faculty of Applied Sciences, 2015)
The objective of this work is to evaluate both physical and mechanical properties of particleboard panels manufactured from oil palm (Elais guineensis) trunks. Besides that, this work also to determine the effect of the different resin content (8%, 10% and 12%) and additional wax (0% and 1%) on the physical and mechanical properties of the board. Modulus of Rupture (MOR), Modulus of Elasticity (MOE), Internal Bonding Strength (IB), Thickness Swelling (TS), Water Absorption (WA) and density of the samples were tested based on Japanese Industrial Standards (JIS A: 5908-2003). Oil palm trunk particleboard made with highest adhesive content give the highest modulus of rupture (MOR), modulus of elastic (MOE) and internal bonding (IB) strength values of 5.80 MPa, 894.73 MPa and 0.07 MPa respectively. Whereas, thickness swelling and water absorption result increase due to the higher urea formaldehyde (UF) adhesive content and additional wax (1%). Additional of wax on the particleboard decreased the mechanical properties but increase in the physical properties of the particleboard.